Visualization research on bubble in overflow sieve plate hot water tower. Issue 6 (28th August 2020) - Bao, Zebin; Wang, Yifei; Yu, Guangsuo; Wang, Fuchen; Xiao, Huixia
Abstract: In this paper, an experimental apparatus was developed based on the evaporating water tower of the circuit bottom‐ash sluicing system. The formation and movement of single bubble that emerged from an orifice with 5 mm diameter in the middle of the tray were investigated by visual experiments, with water flow rates of 150, 200, and 250 L/h −1, steam flow rate of 5 kg/h −1, and nitrogen flow rates of 0.1632 and 0.32645 kg/h −1 . The lifetime of bubbles was recorded by high‐speed camera, and the characteristics of bubble deformation and movement were determined by image processing software Image Pro‐plus. Results showed that the lifetime of bubbles was divided based on the pictures into three parts, namely, formation, region, and oscillation regions. Bubble deformation and movement were assessed in each part. The equivalent radius of bubbles increased rapidly in the first region because of gas influx and grew more slowly in the two latter regions. The aspect ratio of bubbles changed from large to small in the formation region but surged in the oscillation region. The vertical velocity of the centroid of steam bubbles increased at the beginning and then fluctuated. However, the vertical velocity of the centroid of nitrogen bubbles increased over time due to the lack of mass transfer. The hollow phenomenon was found in steam and mixture bubbles through condensation. The effect of noncondensable gases on transmission was also discussed. With increasing nitrogen ratio, the time of formation and oscillation regions decreased for the mixed gas bubbles, leading to the deterioration of heat transfer in the tower. This work provides theoretical guidance for evaporating hot water tower operation.